Coordinating Tissue Regeneration Through Transforming Growth Factor‐β Activated Kinase 1 Inactivation and Reactivation. (14th March 2019) - Hsieh, Hsiao Hsin Sung; Agarwal, Shailesh; Cholok, David J.; Loder, Shawn J.; Kaneko, Kieko; Huber, Amanda; Chung, Michael T.; Ranganathan, Kavitha; Habbouche, Joe; Li, John; Butts, Jonathan; Reimer, Jonathan; et al.
Abstract: Aberrant wound healing presents as inappropriate or insufficient tissue formation. Using a model of musculoskeletal injury, we demonstrate that loss of transforming growth factor‐β activated kinase 1 (TAK1) signaling reduces inappropriate tissue formation (heterotopic ossification) through reduced cellular differentiation. Upon identifying increased proliferation with loss of TAK1 signaling, we considered a regenerative approach to address insufficient tissue production through coordinated inactivation of TAK1 to promote cellular proliferation, followed by reactivation to elicit differentiation and extracellular matrix production. Although the current regenerative medicine paradigm is centered on the effects of drug treatment ("drug on"), the impact of drug withdrawal ("drug off") implicit in these regimens is unknown. Because current TAK1 inhibitors are unable to phenocopy genetic Tak1 loss, we introduce the dual‐inducible COmbinational Sequential Inversion ENgineering (COSIEN) mouse model. The COSIEN mouse model, which allows us to study the response to targeted drug treatment ("drug on") and subsequent withdrawal ("drug off") through genetic modification, was used here to inactivate and reactivate Tak1 with the purpose of augmenting tissue regeneration in a calvarial defect model. Our study reveals the importance of both the "drug on" (Cre‐mediated inactivation) and "drug off" (Flp‐mediated reactivation) states during regenerative therapy using a mouse model with broad utility to study targeted therapies for disease.Stem Cells 2019;37:766–778 Abstract : Manipulating transforming growth factor β‐activated kinase 1 for cell and scaffold free tissue regeneration using a dual‐inducible Combinational Sequential Inversion Engineering mouse model.